دور القيادة الإدارية على تنمية الموارد البشرية دراسة وصفية تحليلية: The Importance of Administrative Leadership in The Context of Development of Human Resources: A Descriptive Analytic Study - Asem Ali Hasan Al-sharafi; Ibrahim Fahad Sulaiman (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص تعد القيادة الإدارية أحد أهم وظائف الإدارة الحديثة إلى جانب عمليات التنظيم والتخطيط والرقابة واتخاذ القرارات، ولكن عند دراسة موضوع القيادة الإدارية نلاحظ أنها تتعلق بجميع وظائف تنمية الموارد البشرية، ومن دونها لا وجود للتنظيم والتخطيط ولا يمكن اتخاذ القرارات الاستراتيجية. وقد تمحورت مشكلة هذه الدراسة حول مدى تأثير القيادة الإدارية على تنمية الموارد البشرية في ظل التوسع والنمو السريع للمنظمات والمؤسسات وتعقدها وزيادة حاجتها إلى المرونه والقدرة على مواجهة المتغيرات والإشكالات المختلفة سوا كانت تنظيمية أو إدارية، وهدفت الدراسة إلى التعرف على دور القيادة الإدارية في تنمية الموارد البشرية في المؤسسات أو التنظيمات المؤسسية، من خلال استخدام المنهج الوصفي والتحليل النظري للكتب والدراسات التي ناقشت القيادة الإدارية وأثرها على تنمية الموارد البشرية، وتوصلت الدراسة إلى أن القيادة الإدارية تمثل الركيزة الأساسية لنجاح المؤسسات وضمان تفوقها وبقائها واستدامتها في ظل التنافس الشديد والكبير في بيئة العمل، كونها تمثل حجر الأساس في توجيه العمليات الإدارية للمؤسسة، ومن خلال القيادة الإدارية الناجحة تستطيع المؤسسة أو المنظمة أن تتفوق وتتميز عن بقية المؤسسات والتنظيمات. الكلمات المفتاحية: القيادة الإدارية، تنمية الموارد البشرية، اتخاذ القرار، الاتصال، التحفيز Abstract Administrative leadership, along with the processes of organization, planning, control, and decision-making, is one of the most significant functions of modern management. When studying administrative leadership, it's important to keep in mind that it encompasses all aspects of human resource development. Additionally, there can be no structure or planning without it as well as strategic decision is impossible without it. The problem statement of the study is to observe how much administrative leadership influences human resource development in light of organizations’ and institutions' rapid expansion and growth, their complexity, and the increased need for flexibility and the ability to deal with a variety of variables and problems, both organizational and administrative. The study aimed to identify the role of administrative leadership in the development of human resources in institutions or institutional organizations using a descriptive approach and theoretical analysis of books and studies that discussed administrative leadership and its impact on human resource development. The study found that administrative leadership is the most important factor in maintaining institutions' supremacy, longevity, and sustainability in view of the strong and high level of rivalry in the work environment as it is the basis for directing the administrative operations of the institution. Moreover, the institution can achieve greatness, survival, and sustainability through effective administrative leadership. Keywords: Administrative Leadership, Human Resource Development, Decision-Making, Communication, Motivation